2012
DOI: 10.1007/s12199-012-0320-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to the intention to leave and the decision to resign among newly graduated nurses: a complete survey in a selected prefecture in Japan

Abstract: Our findings suggest that, while investment in facilities and human capital may have short-term benefits, measures from a long-term perspective are needed for the prevention of future resignations among NGNs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
3
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 26 publications
5
33
3
2
Order By: Relevance
“…Results of the research it supports research conducted by Tominaga (2013) which concluded that the characteristics of the individual effect is significant the intention to leave the research supporting the theory.…”
Section: The Characteristics Of Individual Significant Effect On Intesupporting
confidence: 76%
“…Results of the research it supports research conducted by Tominaga (2013) which concluded that the characteristics of the individual effect is significant the intention to leave the research supporting the theory.…”
Section: The Characteristics Of Individual Significant Effect On Intesupporting
confidence: 76%
“…The findings on the presence of a role model in this study contrasts with previous findings that the presence of a role model consistently influences intention to leave and decision to resign among newly graduated Japanese nurses who were hired in 2008-2009 (categorised in this study within the generation born during the 1980s) [21,23]. This might be influenced by the unique characteristics of 'Generation Yutori' (sophisticated media and computer environment, lacking ambition, etc.)…”
Section: Generation-specific Factorscontrasting
confidence: 99%
“…The present study revealed two factors which have decreased risk of intentions to leave: social support, which was a common generational factor in three generations (those born between 1965 and 1979, in the 1980s, and after 1990), and the presence of a role model, which was a common generational factor for all generations except the one born after 1990. These findings support previous findings regarding social support [20][21][22] and the presence of a role model [21,23], and highlight the need to strengthen human resource support and social support in the workplace, which could be acceptable countermeasures at the hospital level for reducing intention to leave among female nurses.…”
Section: Generation-common Factorssupporting
confidence: 89%
See 2 more Smart Citations